Transition‐Metal Single Atoms Anchored on Graphdiyne as High‐Efficiency Electrocatalysts for Water Splitting and Oxygen Reduction. Issue 9 (7th January 2019) - He, Tianwei; Matta, Sri Kasi; Will, Geoffrey; Du, Aijun
Abstract: Single‐atom catalysts, which can maximize the utility of metal atoms, and at the same time achieve high catalytic performance, have attracted great interest in research. In this present study, 11 transition metal atoms supported on a graphdiyne (GDY) monolayer (TM@GDY, where TM represents a transition metal from Sc to Zn and Pt) as electrocatalysts are investigated by means of first‐principle calculations. It is found that the supported single atom is very stable at the corner of the acetylenic ring. These features can help in the realization of uniformly distributed and well‐ordered single atoms on GDY. Few composites viz Sc@GDY, Ti@GDY, V@GDY, Fe@GDY, and Pt@GDY display high catalytic activity toward hydrogen evolution reaction (HER). Especially for Ti@GDY and V@GDY, both C and TM are active sites which are the best HER catalysts among the studied composites. Moreover, Pt@GDY and Ni@GDY composites can be promising bifunctional electrocatalysts for water splitting [0.01 and 0.46 V for HER and oxygen evolution reaction (OER)] and metal–air‐battery (0.29 and 0.40 V for OER and oxygen reduction reaction) catalysts, respectively. This work demonstrates that GDY is indeed a promising single‐atom support which can be considered for the design of high activity and inexpensive multifunctional electrocatalysts for practical catalytic applications. Abstract : Graphdiyne (GDY) decorated with different single transition metals (TMs) is designed as high‐efficiency and inexpensive electrocatalysts for hydrogen evolution, oxygen evolution, and oxygen reduction reactions. The selected GDY@TM composites exhibit excellent catalytic activity toward one or more reactions, which can be served as promising bifuctional electrocatalysts for experimental realization.